Trade secrets : powerful strategies for volatile markets - Manz, Adrian (Harriman House Ltd, 2013)
A cornerstone strategy for success in the markets Trade Secrets is a uniquely in-depth and advanced trading guide, teaching a complete and winning trading method from start to finish. Packed with exclusive content, it reveals one of master trader Adrian Manz's best trading strategies. The patterns in this book spell opportunity: when applied correctly, the system can be the cornerstone of a profitable trading business. The trade secret at the heart of the book is the expansion-of-range-and-volume set-up. For the first time ever it is explored in full and intricate detail: revealing how and why it works, and demonstrating its utility for day, swing, and position traders. This strategy is portable. It is applicable to multiple time compressions. It is consistently profitable. It is, in other words, not merely a good strategy - but a great one. No one looking to make a living in the markets can afford to be without this handbook to identifying the opportunities it presents and executing them flawlessly.